Protein levels of brain-derived neurotrophic factor in the hippocampus of low/high aerobic capacity rats - Mertikas, Georgios (2010)
Hippocrates and Plato have first documented the connection between a healthy mind and body, during a period which launched analytical thinking and philosophy in Ancient Greece. Modern research has also indicated the contribution of an active lifestyle to enhanced brain performance and decreased incidence of neurodegenerative diseases and mood disorders such as Alzheimer’s disease and depression respectively. This has been hypothesized to emerge through mechanisms which are enhanced by exercise and contribute on brain plas-ticity and health. The Neurotrophins hypothesis implicates several molecules in brain plasticity and healthy aging. Among them, Brain-derived Neurotrophic Factor (BDNF) has been shown to in-crease its expression levels in the most plastic regions of the brain in an activity-dependent manner both in development and adulthood, proposing its significance throughout lifespan. We used Immunohistochemistry (IHC) to investigate the expression of BDNF protein le-vels in the hippocampi of Low/High aerobic capacity rats which have proposed a model of sedentary and active lifestyle. Rats were also subjected to Rotarod motor learning test were the high capacity group showed increased baseline performance and faster learning than the low capacity one. IHC in the hippocampi of the animals didn’t detect any significant differ-ences of BDNF protein levels in CA1 and CA3 areas. The failure to detect differences is believed to emerge due to the sedentary lifestyle in both groups, suggesting that genetic background may not determine the levels of the protein in sedentary conditions.